2017
DOI: 10.1038/s41598-017-10464-1
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Metabolic Flux Analysis of Myeloid-Derived Suppressor Cells Confirms Immunosuppression-Related Metabolic Plasticity

Abstract: Recent years have witnessed an increasing interest at understanding the role of myeloid-derived suppressor cells (MDSCs) in cancer-induced immunosuppression, with efforts to inhibit their maturation and/or their activity. We have thus modelled MDSCs central carbon metabolism and bioenergetics dynamic, calibrating the model using experimental data on in vitro matured mice bone marrow cells into MDSCs. The model was then used to probe the cells metabolic state and dynamics, performing a dynamic metabolic flux an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…50 Dynamic metabolic flux analysis, a unique tool that can quantify extracellular and intracellular nutrient and metabolite concentrations, demonstrated that MDSCs exhibit the Warburg effect during their maturation with high glucose and glutamine uptake rates, a reduced oxygen consumption rate (OCR) and that approximately 95% of the ATP generated was obtained through a glycolysis-dependent mechanism. 51 Tumourderived MDSCs exhibit high glycolysis upregulation, and its metabolite phosphoenolpyruvate could protect MDSCs from apoptosis and contribute to their survival. 38 Owing to the high glucose uptake rates of both tumour cells and MDSCs, immune cells do not have any metabolic elasticity to acclimate to the condition of low oxygen tension and limited glucose availability, which could result in immune cell dysfunction and death, indirectly facilitating tumour escape and progression.…”
Section: Glucose Metabolism In Mdscsmentioning
confidence: 99%
“…50 Dynamic metabolic flux analysis, a unique tool that can quantify extracellular and intracellular nutrient and metabolite concentrations, demonstrated that MDSCs exhibit the Warburg effect during their maturation with high glucose and glutamine uptake rates, a reduced oxygen consumption rate (OCR) and that approximately 95% of the ATP generated was obtained through a glycolysis-dependent mechanism. 51 Tumourderived MDSCs exhibit high glycolysis upregulation, and its metabolite phosphoenolpyruvate could protect MDSCs from apoptosis and contribute to their survival. 38 Owing to the high glucose uptake rates of both tumour cells and MDSCs, immune cells do not have any metabolic elasticity to acclimate to the condition of low oxygen tension and limited glucose availability, which could result in immune cell dysfunction and death, indirectly facilitating tumour escape and progression.…”
Section: Glucose Metabolism In Mdscsmentioning
confidence: 99%
“…A dynamic metabolic flux analysis revealed that a high glycolytic flux is needed for the maturation of MDSCs from bone marrow precursors and suggested an indirect mechanism by which the consumption of carbon sources by MDSCs results in the suppression of effector T cells. 48 Previous results showed that glycolysis promotes MDSC survival in tumorbearing animals by preventing ROS-mediated apoptosis via the antioxidant activity of the glycolytic intermediate phosphoenolpyruvate. 49 Conversely, SIRT1 reprogrammed MDSCs into inflammatory M1 macrophages by shifting them to HIF-1α-dependent glycolysis.…”
Section: The "Warburg" Battle Between Tumor and Myeloid Cellsmentioning
confidence: 99%
“…The metabolic network presented here and displayed in Fig. 3 has been modified from previous models of Chinese Hamster Ovary cells (CHO) and mouse myeloid derived suppressor cells (MD-SCs) 34,3639 . It includes 35 enzymatic reactions describing the fate of 52 metabolites.…”
Section: Methodsmentioning
confidence: 99%